2021
DOI: 10.1167/iovs.62.3.16
|View full text |Cite
|
Sign up to set email alerts
|

Aurora Kinase B Expression, Its Regulation and Therapeutic Targeting in Human Retinoblastoma

Abstract: Aurora kinase B (AURKB) plays a pivotal role in the regulation of mitosis and is gaining prominence as a therapeutic target in cancers; however, the role of AURKB in retinoblastoma (RB) has not been studied. The purpose of this study was to determine if AURKB plays a role in RB, how its expression is regulated, and whether it could be specifically targeted. METHODS. The protein expression of AURKB was determined using immunohistochemistry in human RB patient specimens and immunoblotting in cell lines. Pharmaco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 46 publications
1
15
0
Order By: Relevance
“…In agreement with the existing literature, our data suggest that MYCN promotes RB cell growth and metastasis possibly via regulating the genes involved in the ECM modification. MYCN in addition to the regulation of genes involved in glucose metabolism and migration, has been shown to positively modulate the expression of mitotic protein kinase, aurora kinase B in RB [30] and other tumors [61]. Overall, our data along with the published literature show that MYCN may regulate a plethora of cellular functions in RB and other tumors [62].…”
Section: Discussionsupporting
confidence: 59%
See 2 more Smart Citations
“…In agreement with the existing literature, our data suggest that MYCN promotes RB cell growth and metastasis possibly via regulating the genes involved in the ECM modification. MYCN in addition to the regulation of genes involved in glucose metabolism and migration, has been shown to positively modulate the expression of mitotic protein kinase, aurora kinase B in RB [30] and other tumors [61]. Overall, our data along with the published literature show that MYCN may regulate a plethora of cellular functions in RB and other tumors [62].…”
Section: Discussionsupporting
confidence: 59%
“…Immunoreactivity score was assigned to the tissue specimens showing MYCN expression based on the intensity and extent of expression as described previously [30]. Intensity of MYCN expression was scored as follows; 0 = negative, 1 = low, 2 = medium and 3 = high.…”
Section: Immunohistochemistrymentioning
confidence: 99%
See 1 more Smart Citation
“…Wu et al showed that AURKB silencing promotes apoptosis of osteosarcoma 143B cells through unc-51 like autophagy activating kinase 1 (ULK1) phosphorylation-induced autophagy (25). Recently, it was revealed that AURKB plays an important role in the regulation of mitosis and is gaining prominence as a therapeutic target in RB (26). A previous study overexpressed TOP2A in bladder urothelial carcinoma (BLCA) and concluded that TOP2A represents a diagnostic marker of BLCA (27).…”
Section: Discussionmentioning
confidence: 99%
“…Since AURKA and AURKB contribute to correct mitotic spindle assembly and chromosome segregation (88), these kinases serve critical roles in ensuring mitotic fidelity and their inhibition is lethal for RB1-deficient cancer cells, which upregulate a number of mitotic genes as a result of E2F deregulation (50,51,82). As is the case with other RB1-deficient cancer cells, primary RB tumors display high expression levels of several mitotic genes, including AURKB, polo-like kinase 1 (PLK1), mitotic arrest deficient 2 like 1 and BUB1 mitotic checkpoint serine/threonine kinase (43,44,89,90). Two recent studies have demonstrated that pharmacological inhibition of AURKB and PLK1 in RB cells resulted in cell cycle arrest and increased apoptosis, whereas the effects of the inhibitors on a nontumoral retinal pigment epithelial cell line (ARPE-19) were negligible under identical conditions, which was indicative of a higher sensitivity of RB cells to these inhibitors (89,91).…”
Section: Genome Maintenance Mechanisms In Rbmentioning
confidence: 99%